2021
DOI: 10.1007/s12325-021-01779-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Cost Savings of Continuous Pulse Oximetry and Capnography Monitoring of United States General Care Floor Patients Receiving Opioids Based on the PRODIGY Trial

Abstract: Introduction: Despite the high incidence of respiratory depression on the general care floor and evidence that continuous monitoring improves patient outcomes, the cost-benefit of continuous pulse oximetry and capnography monitoring of general care floor patients remains unknown. This study modeled the cost and length of stay savings, investment breakeven point, and likelihood of cost savings for continuous pulse oximetry and capnography monitoring of general care floor patients at risk for respiratory depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A recent study modeling the costs of continuous monitoring reported a combined pulse oximeter capnography unit to cost $4800 and a disposable pulse oximeter probe and capnography line to cost $8.50 and $14.50, respectively. 61 Telemetry to a central station with around-the-clock human monitoring has substantial costs. Furthermore, using condition-specific monitoring for a surveillance application is expensive and less effective for detecting general condition deterioration early (eg, cardiotelemetry in patients who do not meet American Heart Association criteria).…”
Section: Universal Continuous Monitoring Is Both Affordable and Assoc...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study modeling the costs of continuous monitoring reported a combined pulse oximeter capnography unit to cost $4800 and a disposable pulse oximeter probe and capnography line to cost $8.50 and $14.50, respectively. 61 Telemetry to a central station with around-the-clock human monitoring has substantial costs. Furthermore, using condition-specific monitoring for a surveillance application is expensive and less effective for detecting general condition deterioration early (eg, cardiotelemetry in patients who do not meet American Heart Association criteria).…”
Section: Universal Continuous Monitoring Is Both Affordable and Assoc...mentioning
confidence: 99%
“…Depending on the business model used, estimates to install wireless pulse oximetry hardware range from a $0 out-of-pocket capital cost to $7000 per bed. 61 Sensor costs per patient also vary depending on the type, disposability, and patient length of stay. A recent study modeling the costs of continuous monitoring reported a combined pulse oximeter capnography unit to cost $4800 and a disposable pulse oximeter probe and capnography line to cost $8.50 and $14.50, respectively.…”
Section: Pro Position: Universal Continuous Respiratory Monitoring Of...mentioning
confidence: 99%
“…Fortunately, most episodes of respiratory depression are ‘self-limited’, and do not lead to immediate life-threatening events (e.g., respiratory arrest). However, surgical patients who experience seemingly benign, self-limited episodes of respiratory depression have been found to have increased hospital costs compared to patients who did not have postoperative respiratory depression [8 ▪▪ ,27 ▪ ]. In addition, self-limited episodes of respiratory depression in the postanesthesia recovery unit (PACU) have been associated with increased rates of postoperative pulmonary complications [28] including severe opioid toxicity requiring naloxone administration on wards [29,30].…”
Section: Obstructive Sleep Apnea and Self-limited Postoperative Respi...mentioning
confidence: 99%
“…Capnography, in this context may be especially beneficial for patients on supplemental oxygen who may maintain adequate oxygenation despite hypoventilation [25]. Cost-effectiveness modeling data for continuous monitoring for postoperative hospital floor patients seems favorable in that a mere 2–3% reduction in OIRD episodes has provided a good enough return on investment to ‘break-even’ on the cost of continuous oximetry and capnography monitoring [26 ▪▪ ]. TJC states that hospitals should monitor patients at higher risk for opioid-related adverse outcomes (TJC PC.01.02.07 EP 6) and that appropriate equipment should be available to monitor patients at high risk for opioid-related adverse outcomes (TJC LD.04.03.13 EP 7) [27].…”
Section: Relevance Of Abuse In the Perioperative Periodmentioning
confidence: 99%